A new take on cake : 200 beautiful, doable cake mix recipes for bundts, layers, slabs, loaves, cookies, and more! - Byrn, Anne (Clarkson Potter, 2021)
"The bestselling author of The Cake Mix Doctor updates her beloved approach to creating show-stopping desserts, with 50 modernized classic recipes and 150 brand-new recipes, featuring simple variations for different diets and using today's most popular flavors. When Anne Byrn's The Cake Mix Doctor first appeared two decades ago, it amassed a cult following by delivering exactly what people wanted and needed: a shortcut for delicious and beautiful cakes that appeared to be from scratch that wouldn't take all the time they didn't have in their busy days. Since then, our lives have only gotten more frantic, and our palates have only gotten more discerning. Now Anne presents A New Take on Cake, which allows you to take just a little time and only a few ingredients to turn a mix into a masterpiece. Inspired by the shifting landscape of the baking aisle, Anne has updated the way she bakes using not only natural cake mixes but also more olive oil instead of butter to create healthier cakes and cakes with more volume and better texture. Influenced, too, by modern flavor profiles like tahini and blood orange while staying true to the always-loved classics like chocolate and coffee, the recipes here are sure to please adventurous eaters as well as the traditionalists. With variations between simple sheet and loaf cakes, big cake projects, and decadent layer cakes, tortes, and more, even vegan and gluten-free options, these cakes are perfect for today's busy home baker"--